Overcoming the Limits of Ejection Fraction and Ventricular-Arterial Coupling in Heart Failure - Antohi, Elena-Laura; Chioncel, Ovidiu; Mihaileanu, Serban (Frontiers in Cardiovascular Medicine, 2022)
Left ventricular ejection fraction (LVEF) and ventricular-arterial coupling (VAC) [VAC = Ea/Ees; Ea: effective arterial elastance; Ees: left ventricle (LV) elastance] are both dimensionless ratios with important limitations, especially in heart failure setting. The LVEF to VAC relationship is a divergent non-linear function, having a point of intersection at the specific value of 0.62, where V0 = 0 ml (V0: the theoretical extrapolated value of the volume-axis intercept at end-systolic pressure 0 mmHg). For the dilated LV, both LVEF and VAC are highly dependent on V0 which is inconclusive when derived from single-beat Ees formulas. VAC simplification should be avoided. Revisiting the relationship between systolic time intervals (STI), pressure, and volumes could provide simple-to-use guiding formulas, affordable for daily clinical practice. We have analyzed by echocardiography the hemodynamics of 21 patients with severe symptomatic heart failure with reduced ejection (HFrEF) compared to 12 asymptomatic patients (at risk of heart failure with mild structural disease). The groups were unequivocally separated by ‘classic’ measures (LVEF, LV end-systolic volume (ESV), LV mass, STI). Chen's Ees formula was weakly correlated with LVEF and indexed ESV (ESVi) but better correlated to the pre-ejection period (PEP); PEP/total ejection time (PEP/TET); systolic blood pressure/PEP (SBP/PEP) (P < 0.001). Combining the predictability of the LVEF to the determinant role of SBP/PEP on the Ees variations, we obtained: (SBP*LVEF)/PEP mm Hg/ms, with an improved R2 value (R2 = 0.848; P < 0.001). The strongest correlations to VAC were for LVEF (R = −0.849; R2 = 0.722) and PEP/TET (R = 0.925; R2 = 0.857). By multiple regression, the VAC was strongly predicted (N = 33): (R = 0.975; R2 = 0.95): VAC = 0.553–0.009*LVEF + 3.463*PEP/TET, and natural logarithm: Ln (VAC) = 0.147–1.4563*DBP/SBP*0.9–0.010*LVEF + 4.207*PEP/TET (R = 0.987; R2 = 0.975; P = 0) demonstrating its exclusive determinants: LVEF, PEP/TET, and DBP/SBP. Considering Ea as a known value, the VAC-derived Ees formula: Ees_d ≈ Ea/(0.553–0.009*LVEF+3.463*PEP/TET) was strongly correlated to Chen's Ees formula (R = 0.973; R2 = 0.947) being based on SBP, ESV, LVEF, and PEP/TET and no exponential power. Thus, the new index supports our hypothesis, in the limited sample of patients with HFrEF. Indices like SBP/PEP, (SBP*LVEF)/PEP, PEP/TET, and DBP/SBP deserve further experiments, underlining the major role of the forgotten STI.